(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article provides a scientific and philosophical analysis of the development strategy for the further development of the Republic of Uzbekistan as a socio-cultural technology, which is the basis for the development of the state and society. It also studies the integration of socio-cultural technologies with spiritual life in society, in particular with the Strategy of Actions and the Strategy of Development, as a means of achieving people’s well-being.